Lotus root‐like appearance in the left anterior descending artery treated with a drug‐coated balloon angioplasty. Issue 7 (18th July 2022) - Takagi, Wataru; Okada, Tomoaki; Nosaka, Kazumasa; Miyoshi, Toru; Doi, Masayuki
Abstract: A lotus root‐like appearance of the coronary artery diagnosed by optical coherence tomography (OCT) is characterized by old coronary thrombi that form small lumen channels. Herein, serial OCT images of a left anterior descending artery with a lotus root‐like appearance, treated with drug‐coated balloon angioplasty are described. Abstract : Drug‐coated balloon angioplasty may be a useful treatment for coronary lesions with lotus root‐like appearances.